2017
DOI: 10.1111/faam.12146
|View full text |Cite
|
Sign up to set email alerts
|

Accountability and not‐for‐profit organisations: Implications for developing international financial reporting standards

Abstract: This paper provides empirical evidence which informs contemporary debates on developing international financial reporting standards for not‐for‐profit organisations (NPOs). Drawing on a global survey with respondents showing experience of NPO reporting in 179 countries, we explore: practice and beliefs about NPO financial reporting internationally; perceptions of accountability between NPOs and stakeholders; and implications for developing international financial reporting standards. Interpreting our research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 39 publications
3
66
0
Order By: Relevance
“…We find that, despite users' needs often being alluded to in the financial reporting framework (Young, 2006), our respondents highlight that the users (stakeholders) who appear to be prioritised are the regulators or standard-setters themselves. The survey results show that, similarly to other's findings (for example, Coule, 2015;Crawford et al, 2018;Ryan et al, 2014) beneficiaries' needs do not drive NPO reporting, as they are not seen as powerful influencers on NPO financial reporting. Yet beneficiaries need power to bring their needs to dominance (Mitchell et al, 1997), especially if those with power are unwilling to negotiate change (Reay & Hinings, 2009).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We find that, despite users' needs often being alluded to in the financial reporting framework (Young, 2006), our respondents highlight that the users (stakeholders) who appear to be prioritised are the regulators or standard-setters themselves. The survey results show that, similarly to other's findings (for example, Coule, 2015;Crawford et al, 2018;Ryan et al, 2014) beneficiaries' needs do not drive NPO reporting, as they are not seen as powerful influencers on NPO financial reporting. Yet beneficiaries need power to bring their needs to dominance (Mitchell et al, 1997), especially if those with power are unwilling to negotiate change (Reay & Hinings, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…Crawford et al, 2018 present an accountability matrix for NPOs which locates stakeholder groups according to their internal or external relationship with the NPO and the nature of the accountability The extent to which these users depend on financial reports for accountability and decisionmaking varies, with government and large funders (including lenders) demanding financial reporting more than public donors. Crawford, Morgan and Cordery (2018) found support amongst NPO stakeholders who were involved in NPO financial reporting for exercising broad stewardship accountability. Yet they also found that accountability upwards to external funders and regulators was prioritised.…”
Section: (Iii) Which Users Drive/ Decide the Type Of Financial Reportmentioning
confidence: 99%
“…The UK SORP could, then, act as a base (recognised as acceptable under IFRS) for international co-ordination of cooperative accounting. The UK charity SORP is closely aligned with Generally Accepted Accounting Practice for notfor-profits and there is currently a movement developing towards international alignment of national practices in not-for-profit accounting (Crawford et al, 2018). In practice, the international SORP would be international Generally Accepted Accounting Practice guidelines for co-operatives, which would be aligned with the UK SORP if the two projects are well co-ordinated as both are developed.…”
Section: Practical Research Agenda To Develop a Sorp For Co-operativesmentioning
confidence: 99%
“…This research topic was chosen because there is general public interest in the accountability of nonprofit organisations and the underlying issues are of broad importance to society. In recent years, there has been an abundance of research on nonprofit accountability (Crawford, Morgan, & Cordery, 2018;O'Leary, 2017). Given recent scandals that have occurred in all types of organisations; at the corporate level (e.g.…”
Section: List Of Figuresmentioning
confidence: 99%
“…Figure 1-1 conceptualises where the nonprofit sector fits within the economic sectors. See also Crawford et al (2018) and Salamon and Sokolowski (2016) for other visual schematics of economic sectors.…”
Section: Definition and Characteristics Of Nonprofit Organisationsmentioning
confidence: 99%